LEXICAL-SEMANTIC INTERPRETATION OF ARABIC BORROWINGS IN EXPLANATORY DICTIONARIES OF ALISHER NAVOI'S WORKS - Rayhonoy Goyibboyeva Ahmadjonovna (Web of Journals Publishing, 2026)
This article provides a detailed analysis of the sign-semasis of Arabic borrowings found in explanatory dictionaries compiled for the works of Alisher Navoi. These borrowings—lexemes that express personal and object-related attributes (such as moral and psychological traits, appearance, color, and taste)—are examined from lexical-semantic, lexical-syntactic, and stylistic perspectives. In addition, the paper explores the contextual dependence of positive and negative character traits and their adaptation to the Uzbek language system.
Keywords: Dictionary, borrowing, Arabisms, sign-semasis, personal-character traits, appearance, mentality, color, taste, positive feature, negative feature, adaptation.